Funding for China’s Top Universities: Does Size Matter? - S. S. Donetskaya; Liang Bin (Высшее образование в России)
Over the past thirty years, thanks to government initiatives for the “construction” of world-class universities, a cohort of elite (leading) universities has been created in China, covering about 5 % of universities, which have tangible advantages over other universities in student recruitment, teaching, research, funding, and support from local authorities. Despite the similar possibilities gained by universities when they transition to the status of elite institutions, each of them has a different budget structure and distinct operational results, which are primarily associated with the positions of universities in international rankings.   Therefore, the aim of the article is to show whether increased investment in development really allows Chinese universities to be successful in the ranking race.   The article describes the sources of funding for Chinese universities, shows the funding structure of some leading institutions, and presents a model of funding for state universities. Special attention is paid to factors affecting the level of funding for Chinese universities, such as belonging to the elite group of universities, geographical location, and the range of educational programs implemented. Based on a sample of 29 leading universities, it is shown that the diversity of funding sources is an indicator of success: as a rule, the best universities have a higher share of income from entrepreneurial activities. At the same time, the volume of the university budget only 50 % determines advancement in rankings. The second reason for success is the “symbolic capital” obtained by universities from participation in the 211 / 985 / “Double First Class” projects, which allows them to achieve significant competitive advantages. Sources of information for analysis included: data from the Ministry of Education of China, web-sites of leading Chinese universities, publications available in the open access network of the Chinese internet, as well as scientific articles published in Russian and leading world publications.